From Observation to Information and Users: The Copernicus Marine Service Perspective - Le Traon, Pierre Yves; Reppucci, Antonio; Alvarez Fanjul, Enrique; Aouf, Lotfi; Behrens, Arno; Belmonte, Maria; Bentamy, Abderrahim; Bertino, Laurent; Brando, Vittorio Ernesto; Kreiner, Matilde Brandt; Benkiran, Mounir; Carval, Thierry; et al. (Frontiers in Marine Science, 2019)
The Copernicus Marine Environment Monitoring Service (CMEMS) provides regular and systematic reference information on the physical and biogeochemical ocean and sea-ice state for the global ocean and the European regional seas. CMEMS serves a wide range of users (more than 15,000 users are now registered to the service) and applications. Observations are a fundamental pillar of the CMEMS value-added chain that goes from observation to information and users. Observations are used by CMEMS Thematic Assembly Centres (TACs) to derive high-level data products and by CMEMS Monitoring and Forecasting Centres (MFCs) to validate and constrain their global and regional ocean analysis and forecasting systems. This paper presents an overview of CMEMS, its evolution, and how the value of in situ and satellite observations is increased through the generation of high-level products ready to be used by downstream applications and services. The complementary nature of satellite and in situ observations is highlighted. Long-term perspectives for the development of CMEMS are described and implications for the evolution of the in situ and satellite observing systems are outlined. Results from Observing System Evaluations (OSEs) and Observing System Simulation Experiments (OSSEs) illustrate the high dependencies of CMEMS systems on observations. Finally future CMEMS requirements for both satellite and in situ observations are detailed.